Porozumienia branżowe w rolnictwie w prawie francuskim i włoskim (zagadnienia wybrane) - Perzyna, Andrzej (Wydawnictwo Naukowe UAM, 2007)
Branch agreements are widely discussed in the foreign literature, particularly in France and Italy. Polish researches have not, as yet, given that subject a serious attention, hence a certain gap in the Polish doctrine exists, which is even more pronounced in the situation today, where branch agreements play a significant role in the organisation of agricultural markets. Shedding some light on the subject in question to the Polish Reader seems therefore useful and justified. The paper covers the key issues related to a branch agreement, and in particular it focuses on its definition, its subject and contents as well as its functions and objectives. The paper concludes with a statement that branch agreements in agriculture constitute a specific legal institution and cannot be classified using the existing system of legal relations. At the same time, the specific features o f that institution require that more focus and attention is given to those agreements, especially when it comes to the deliberations concerning modernisation of Polish agriculture. What may become o f use here is experience gained from the existing branch agreement in the sugar market.
MULTIFUNCTIONAL AGRICULTURAL ENTERPRISE IN ITALIAN LAW